A Review on Conceptual Study Of Concocted Poison: Garavisha - Jaglan, Nisha (International Research Journal of Ayurveda & Yoga, 2022)
Poison causes concern to all living beings by making organism grievously ill, its functioning and leading to death in certain cases. One of the hidden poisons is the concocted poison known as Gara visha. In ayurveda the Gara visha is considered as one of the forms of Kritrimvisha which gets formed by combination of two or more than two poisonous or non-poisonous drugs and affects the whole body by vitiating all the dhatus in the body. We unknowingly consume various combination substances which are harmful to our health. The insect powder, human waste product or some of the agents of Gara visha. This study aims to establish that Gara Visha has significant role in causing toxic symptoms due to its various uses in present society and Ayurveda offers its effective management.